Introducing the Ordinal Turnover Intention Scale (OTIS): A cross-sectional validation in Italian employees and foundation for longitudinal research - Debora BERTOLINI; Francesco MARCATTO (Journal of Health and Social Sciences)
Introduction: Employee turnover represents a critical challenge for organizations, impacting productivity, costs, and workplace stability. Traditional measures of turnover intention typically assess its intensity but fail to capture its dynamic and multi-stage nature. The present study introduces and provides a preliminary validation of the Italian version of the Ordinal Turnover Intention Scale (OTIS), a new tool designed to capture the employees’ position within the turnover decision-making process. Methods: A cross-sectional study was conducted using an online survey platform. Participants (N = 303 Italian employees) completed the OTIS, along with a traditional turnover intention measure and validated scales assessing job satisfaction, work engagement, and occupational stress. Reliability was assessed using the correction for attenuation formula for single-item measures, and construct validity was evaluated using confirmatory factor analysis (CFA). Criterion validity was examined through correlational analyses. Ordinal logistic regression and path analysis were performed to explore the relationships among turnover intention and its antecedents, based on the Job Demands-Resources model. Results: Findings demonstrated that the OTIS categories align with the expected progression of turnover intention. The scale exhibited good reliability and convergent validity, as evidenced by its correlation with the traditional turnover intention measure. Criterion validity was further supported by the associations between OTIS scores and known antecedents of turnover intention. Path analysis revealed that work engagement and occupational stress influenced turnover intention indirectly through their effects on job satisfaction. Discussion: The OTIS provides a simple yet flexible approach to assessing turnover intention, improving upon traditional intensity-based measures. Its ability to capture the dynamic nature of turnover intention holds promise for both researchers and organizations seeking to understand and mitigate voluntary employee departures. A longitudinal study is ongoing to further evaluate its predictive validity.